Black Feminism Reflected through The Narrator’s Responses of Women Oppression In Maya Angelou’s Memoir: A Letter To My Daughter - Elly Santi Pertiwi; Ni Luh Putu Rosiandani (Journal of Language and Literature, 2022)
Any unjust situation where one group denies another group is considered as oppression. This condition is possibly initiated by groups that assume their internal attribute as superior to another group. Therefore, the groups assume they have the right to deny another group's rights. Women oppression is one of kinds of oppression. The differences in physical and biological features of a woman's body benefit men with more privilege and no responsibility to carry children. As a result, a woman is considered as not necessarily need education and career path. A movement has arisen to defense oppressed women, especially women of color, whose experiences are not represented through the mainstream feminist movement. Black feminism's distinctive perspective sees oppression as an intersection of factors. This article aims to elaborate Black feminist perspective toward women oppression in Maya Angelou’s memoir entitled A Letter To My Daughter. The oppression experienced by Black women is identified in the form of the control of Black women images and the regulation of Black women bodies. The narrator’s critical perspective toward the oppression is articulated through her action in promoting self-definition and self-valuation to Black women. Self-empowerment enables Black women to resist and oppose any forms of oppression.